The Effect of Giving Jackfruit (Artocarpus heterophyllus) Leaves Crude Extract as An Alternative Antibacterial of Edwardsiella tarda Bacteria In Vitro - Tania Nilakandhi; Arief Prajitno; Mohammad Fadjar; Desy Amalia Hidayati; Giri Pratama (Department of Aquaculture, 2023)
Barriers to cultivation activities are disease attacks, one of which is caused by infection with the bacterium Edwardsiella tarda. Treatment efforts can be made using natural ingredients such as jackfruit (A. heterophyllus) leaves. This study aims to determine the content of antibacterial compounds in the jackfruit (A. heterophyllus) leaves crude extract and their effect on Edwardsiella tarda bacteria in vitro. The inhibition test used disc test with five different concentrations of jackfruit (A. heterophyllus) leaves crude extract with three replications: 75 mg/L, 150 mg/L, 225 mg/L, 300 mg/L and 375 mg/L with a comparison using two types of controls (positive with 5 mg/L chloramphenicol antibiotics and negative with no treatment) using Tryptone Soy Agar (TSA) media and incubated for 2x24 hours. The results of phytochemical screening proved that the jackfruit (A. heterophyllus) leaves crude extract contains flavonoids, alkaloids, tannins and saponins. Treatment E with a dose of 375 mg/L gave the highest inhibition of 7.80 mm and treatment A with a dose of 75 mg/L gave the lowest inhibition of 4.38 mm. The relationship between the treatment given to the test parameter in the form of the resulting inhibitory power obtained the equation y = 0.0111x + 3.6297 with an R2 value of 0.974 which means 97% of the treatment given in the form of crude extract of jackfruit (A. heterophyllus) leaves affects inhibition of bacteria E. tarda.